Importance of side-chain anchoring atoms on electron donor/fullerene interfaces for high-performance organic solar cells. Issue 19 (2nd May 2017) - Han, Guangchao; Guo, Yuan; Duan, Ruihong; Shen, Xingxing; Yi, Yuanping
Abstract : For the first time, side-chain anchoring atoms are found to play an important role in tuning the donor/fullerene interfacial arrangements and charge-transfer processes for organic solar cells. Abstract : Side-chain engineering is crucial to improve the performance of solution-processed organic solar cells. However, the correlation between side-chain structures and photovoltaic properties is still unclear. Here, we have investigated the local interface morphologies of PC71 BM blended with two donors, DR3TBDT and DR3TSBDT with alkyloxy and alkylthio side chains on the BDT core, by means of atomistic molecular dynamics simulations. Compared with alkyloxy, alkylthio exhibits larger steric hindrance after changing the side-chain anchoring atom from oxygen to sulfur, leading to an obvious reduction of the PC71 BM–BDT face-on orientations in which charge recombination is demonstrated to be the most severe by quantum-chemical calculations. This suggests that the performance of DR3TBDT/PC71 BM solar cells is likely to be more affected by charge recombination than that of DR3TSBDT/PC71 BM-based devices. For the first time, our work unravels the important role of side-chain anchoring atoms in tuning the donor/fullerene interfacial arrangements toward high-performance organic solar cells.